HUBUNGAN ANTARA KESEPIAN DAN KONTROL DIRI DENGAN INTENSITAS BERMAIN GAME ONLINE PADA SISWA DI YOGYAKARTA - Kurnisari, Mitta (Universitas Palangka Raya, 2021)
In an era that is completely online like today, many things can be done online, one of which is playing online games. Loneliness is one of the reasons someone chooses to play online games to pass the time. Ease of access increasingly supports online games attracting many people, including students. But unfortunately the freedom of access can be a problem if students do not have good self-control. Therefore, this study aims to determine the relationship between loneliness and self-control with the intensity of playing online games in students. The approach used in this research is a quantitative approach with the type of correlational research. The results showed that there was a positive and significant relationship between loneliness and the intensity of students playing online games. So it can be concluded that the higher the individual's level of loneliness, the higher the intensity of playing online games. The results also showed that there was a significant negative relationship between self-control and the intensity of students playing online games. That is, the lower the self-control that students have, the higher the intensity of playing online games.